Sensation drama, 1860-1880 : an anthology - Hofer-Robinson, Joanna; Palmer, Beth, 1982- (Edinburgh critical editions of nineteenth-century texts., 2019)
This pioneering edition provides access to some of the most popular plays of the nineteenth century.